2009
DOI: 10.1111/j.1365-246x.2008.03818.x
|View full text |Cite
|
Sign up to set email alerts
|

Response of the ionosphere to the seismic trigerred acoustic waves: electron density and electromagnetic fluctuations

Abstract: S U M M A R YWe study the excitation of low-frequency (0.001-10 Hz) electromagnetic and density fluctuations in the ionosphere during the passage of seismic triggered acoustic waves (AWs). The study involves the generation of ionospheric currents by AWs and subsequent perturbations of the electromagnetic fields and ion and electron density. In this study, the non-local analysis of the fluctuations is carried out in the framework of hydromagnetic theory. Our objective is to examine the spatial and frequency dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 40 publications
(61 reference statements)
1
41
0
Order By: Relevance
“…Employing 1-D and 3-D normal-mode modelling, Artru et al (2004) showed that the surging time and amplitude of ionospheric response are similar in 1-D and 3-D approaches. This is expected since the low-latitude ionospheric change is mainly governed by the infrasonic wind component perpendicular to the magnetic field (Kherani et al, 2009). On this basis, the results in the present study of 1-D modelling are reasonable to the first order.…”
Section: Discussion and Concluding Remarkssupporting
confidence: 74%
“…Employing 1-D and 3-D normal-mode modelling, Artru et al (2004) showed that the surging time and amplitude of ionospheric response are similar in 1-D and 3-D approaches. This is expected since the low-latitude ionospheric change is mainly governed by the infrasonic wind component perpendicular to the magnetic field (Kherani et al, 2009). On this basis, the results in the present study of 1-D modelling are reasonable to the first order.…”
Section: Discussion and Concluding Remarkssupporting
confidence: 74%
“…The divergence-free current density condition ∇·δJ =0 implies ∇·δE=0 (Kherani et al, 2009c). The unstable GRTI wave is low-frequency wave (Kelley, 1989) for which the second term in the above equation can be ignored.…”
Section: Appendix Amentioning
confidence: 99%
“…It is known that IGWs of tropospheric origin produce this kind of amplitudes. These amplitudes are also obtained by using a realistic simulation of the IGWs during the Sumatra tsunami (Occhipinti et al, 2006(Occhipinti et al, , 2008Alam Kherani et al, 2009). Wind measurements in the lower thermosphere (MLT-radar for example) have measurement errors of ∼10 m s −1 (Forbes et al, 1999).…”
Section: The Formation Of the Ionospheric Precursors By Seismogenic Ementioning
confidence: 99%